X ans de l'Elac. - Butheau, Robert; Ceysson, Bernard; Charre, Alain; Cierniewski, Jean-Michel; Claverie, Jean; Deroudille, René; Gérôme, Elyane; Jeune, Marie-Claude; Lerrant, Jean-Jacques; Mure, André; Peizerat, Jacques; Plassard, Odile; et al. (Lyon : ELAC - Espace Lyonnais d'Art Contemporain, 1996)
Vostell, Wolf ; Rousse, Georges ; Viallat, Claude ; Grand, Toni ; Tschumi, Bernard ; Burgin, Victor ; Cluzel, Jean-Pierre ; Giorda, Patrice ; Kelek ; Garnier, Maurice ; Beaudroit, Juliette ; Carlotti, Jean-Albert ; Peizerat, Jacques ; Seror, Louis ; Cane, Louis ; Viollet, Catherine ; Boulerot, Alain ; Monot, E.N.O.S. . Jean-Charles ; Giard, Jean-Pierre
biografie
X ans de l'ELAC, ELAC - Espace Lyonnais d'Art Contemporain, Lyon, exposition du 10 octobre au 25 novembre 1986
Frans
boek